Use of models for identification of nitrogen fertilization strategies for filling feeding gaps of cow-calf systems in the Flooding Pampas of Argentina - Berger, Horacio (2025)
CONTEXT: Nitrogen availability is the primary limitation for the growth of tall fescue, Argentina's most widely cultivated cool-season pasture. Significant yield gaps exist in fescue pastures on commercial farms, where average annual yields are around 5 t/ha, compared to a potential yield of 10 to 15 t/ha. Nitrogen fertilization remains uncommon among cow-calf producers, highlighting the need for a deeper understanding of the complex interactions between nitrogen fertilizer management, stocking rate, and grazing management at the whole-farm level. Considering annual and inter-annual variations in pasture growth could enable regional beef producers to make more informed decisions, improving pasture yield potential, utilization, and overall farm profitability. OBJECTIVES: I) to identify if N fertilization in autumn can boost pasture growth rates as reliable source of extra feed in autumn and winter, taking into account climate variability, and II) to assess how this affects farm-level productivity and profitability. METHODS: An integrated modelling approach, combining a pasture model with a farm system beef cattle model, was employed. Various N fertilizer options (specifically, 100 kg N/ha applied in either autumn or spring) were allocated to 20 % and 40 % of farm areas, across stocking rates ranging from 0.9 to 1.3 head/ha. Simulations were conducted over the long term (1993–2013), focusing on tall fescue pasture growth. Seasonal pasture growth curves were calculated for each year, with particular attention given to identifying average years as well as those with dry autumns or dry springs. RESULTS AND CONCLUSIONS: In average years, increasing the stocking rate by 44 %, from 0.9 head/ha to 1.3, led to a 34 % increase in live weight production in weaner calves and improved gross margins by 30 %. Applying 100 kg N/ha to 20 % of the cow-calf farm, either in autumn or spring, enabled a stocking rate of 1.1 head/ha (a 22 % increase), sustaining gross margins even during dry seasons. Autumn fertilization produced a substantial residual yield response, with an average increase of +1.43 tons/ha in the following spring, and finally Expanding the fertilized area from 20 % to 40 % of the farm did not provide additional economic benefits. SIGNIFICANCE: This study provides valuable, forward-looking insights into how nitrogen fertilization strategies can improve productivity and profitability of cow-calf farms in the Flooding Pampas, especially under variable seasonal climate conditions. While limitations and areas for future research are acknowledged, the findings may also offer practical guidance for boosting livestock productivity in similar environments.